Experimenting with Ethnography : A Companion to Analysis. - Ballestero, Andrea. (Experimental Futures Ser., 2021)
An indispensable guide for all ethnographers, Experimenting with Ethnography collects twenty-one essays that offer concrete suggestions for thinking about and doing ethnographic research and writing.